Nuclear Factor-κB Dysregulation and α-Synuclein Pathology: Critical Interplay in the Pathogenesis of Parkinson’s Disease - Bellucci, Arianna; Bubacco, Luigi; Longhena, Francesca; Parrella, Edoardo; Faustini, Gaia; Porrini, Vanessa; Bono, Federica; Missale, Cristina; Pizzi, Marina (Frontiers in Aging Neuroscience, 2020)
The loss of dopaminergic neurons of the nigrostriatal system underlies the onset of the typical motor symptoms of Parkinson’s disease (PD). Lewy bodies (LB) and Lewy neurites (LN), proteinaceous inclusions mainly composed of insoluble α-synuclein (α-syn) fibrils are key neuropathological hallmarks of the brain of affected patients. Compelling evidence supports that in the early prodromal phases of PD, synaptic terminal and axonal alterations initiate and drive a retrograde degeneration process culminating with the loss of nigral dopaminergic neurons. This notwithstanding, the molecular triggers remain to be fully elucidated. Although it has been shown that α-syn fibrillary aggregation can induce early synaptic and axonal impairment and cause nigrostriatal degeneration, we still ignore how and why α-syn fibrillation begins. Nuclear factor-B (NF-B) transcription factors, key regulators of inflammation and apoptosis, are involved in the brain programming of systemic aging as well as in the pathogenesis of several neurodegenerative diseases. The NF-B family of factors consists of 5 different subunits (c-Rel, p65/RelA, p50, RelB, p52) which combine to form transcriptionally active dimers. Different findings point out a role of RelA in PD. Interestingly, the nuclear content of RelA is abnormally increased in nigral dopamine (DA) neurons and glial cells of PD patients. Inhibition of RelA exert neuroprotection against (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) MPTP and 1-methyl-4-phenylpyridinium (MPP+) toxicity, suggesting that this factor decreases neuronal resilience. Conversely, the c-Rel subunit can exert neuroprotective actions. We recently described that mice deficient for c-Rel develop a PD-like motor and non-motor phenotype characterized by progressive brain α-syn accumulation and early synaptic changes preceding the frank loss of nigrostriatal neurons. This evidence supports that dysregulations in this transcription factors may be involved in the onset of PD. This review highlights observations supporting a possible interplay between NF-B dysregulation and α-syn pathology in PD, with the aim to disclose novel potential mechanisms involved in the pathogenesis of this disorder.